The ANALYSIS OF TEACHER’S LESSON PLAN IN IMPLEMENTING SCIENTIFIC BASED LEARNING FOR YOUNG LEARNER IN PRIMARY SCHOOL - Ina Rohiyatussakinah (Journal of English Language Teaching and Literature (JELTL), 2021)
Lesson plan is an important for teacher as part of guidance and instructional design which consist of necessary aspect such as (goal, objectives, media, and activities until assessment). This paper examines or investigation of the aspect taken in the lesson plan in implementing scientific approach. Lesson plan written by English teacher in primary school, were analyzed using qualitative method and descriptive case study as its framework. The data were obtained from document analysis. Theories from Brown (2001) and Richard (2001) were adapted in analyzing the documents. The result showed that the lesson plan contained the necessary aspect; the activities indicated scientific based learning, teacher were aware of the importance of designing English lesson in which all five aspect (goals, objectives, activities, media and assessment), teacher were able to make goals which measurable, objectives were corresponding with receptive goal, media were practical, effective, efficient, and appropriative for children However, improvements are needed pointed out from this study in accordance to the teacher’s implementation of scientific based learning to sixth students of primary school level, there it seems that scientific based learning could not be effectively applied by the teacher but it somehow gave the some positive contribution to the student participation and critical thinking as in questioning stage and communicating stage.